Peran Da’i dalam Meningkatkan Pemahaman Agama di Kalangan Remaja Kelurahan Mulia Agung Kecamatan Banyuasin III Kabupaten Banyuasin - Ayu Wahyuni; Kusnadi Kusnadi; Emi Puspita Dewi (ScidacPlus, 2023)
This research is entitled The Role of Preachers in Improving Religious Understanding among Youth in Mulia Agung Village, Banyuasin III District, Banyuasin Regency. As a background for the efforts of the preachers to be able to convey the message of the preacher with topics and themes that are close to the daily activities experienced by teenagers so that it is easier for teenagers to understand the messages conveyed and the da'wah will continue to develop and not be boring. The formulation of the problem is 1) what is the description of youth in the Mulia Agung Village? and 2) What is the role of the da'i in increasing religious understanding among youth in the Mulia Agung Village, Banyuasin III District, Banyuasin Regency? This type of research is qualitative research. With data collection techniques including observation, interviews and documentation. This study uses role theory (Role Theory), namely as a theory of integration of orientation, as well as religious disciplines which will be conveyed to mad'u. The results of this study indicate that 1) The description of adolescents in the Mulia Agung Sub-District, namely that adolescents feel bored with the material presented is passive and not modern. Teenagers studying al-Muhajirin need tausiyah to develop and provide closeness to the development of adolescent association in general, then teenagers wish that the studies played by the dai can increase the motivation and enthusiasm of the teenagers themselves. 2) The role of the preacher in increasing religious understanding among young people of the Mulia Agung Sub-District has been maximized and innovative, where the study of the Al-Mujahirin preachers has conveyed the preaching in accordance with the development of today's youth environment and is not monotonous, so that teenagers are excited to listen to the lectures delivered by the preachers so as to increase religious understanding which can shape patterns of interpersonal and group communication to become well-mannered and knowledgeable Muslim youth